Validation of the late-life function and disability instrument in people living with chronic obstructive pulmonary disease: a clinical trial - Blondeel, Astrid; Demeyer, Heleen; Alcaraz-Serrano, Victoria; Buttery, Sara C.; Buekers, Joren; Chynkiamis, Nikolaos; Josa-Culleré, Alícia; Delgado-Ortiz, Laura; Frei, Anja; Glorie, Lies; Gimeno-Santos, Elena; Hopkinson, Nicholas S.; et al. (Annals of the American Thoracic Society, 2025)
Rationale: Disability and loss of function are acknowledged as important problems for people living with chronic obstructive pulmonary disease (COPD), but there is a need for validated tools to assess them.Objectives: The Late-Life Function and Disability Instrument (LLFDI) was originally validated for community-dwelling older adults. The full instrument has not been validated to assess disability and loss of function in people with COPD. Methods: People with COPD from six European countries completed the LLFDI as part of an observational study. Its validity was assessed in terms of 1) levels and distribution of LLFDI domain and subdomain scores; 2) floor and ceiling effects; 3) instrument structure (three domains, seven subdomains) by confirmatory factor analysis; and 4) construct validity by convergent validity, which is based on Spearman correlation with COPD-relevant and related constructs (functional exercise capacity, severity of dyspnea, and COPD-related health status), and known-groups validity, which is based on the distribution of LLFDI scores according to COPD-meaningful groups (disease severity, age groups, and use of a walking aid). Results: The study included 605 participants (ages 68 ± 8 yr, 37% female; FEV1 = 54 ± 20 % predicted). Most had impaired disability and function levels. We observed no floor effects and a ceiling effect in only two subdomains. Confirmatory factor analysis showed a moderate model fit for all LLFDI domains. Most of the correlations met our hypotheses (73%), with moderate to strong correlations for the function domain (rmin-max = 0.25–0.70), followed by the disability limitation domain (rmin-max = 0.15–0.54), and weakest correlations in the disability frequency domain (rmin-max = 0.04–0.41). The disability limitation and function domains differed by disease severity, age group, and use of a walking aid. The disability frequency domain differed by disease severity and use of a walking aid, but not by age groups. Conclusions: The LLFDI, a valid patient-reported outcome to investigate disability and function, has proven good construct validity in people with COPD. Clinical trial registered with the ISRCTN registry (ISRCTN no. 12051706); https://www.isrctn.com/ISRCTN12051706.
Gesehen am 05.08.2025